2018
DOI: 10.3390/d10040127
|View full text |Cite
|
Sign up to set email alerts
|

Marine Heterobranchia (Gastropoda, Mollusca) in Bunaken National Park, North Sulawesi, Indonesia—A Follow-Up Diversity Study

Abstract: Bunaken National Park has been surveyed for a fourth time in 14 years, in an attempt to establish the species composition of heterobranch sea slugs in a baseline study for monitoring programs and protection of this special park. These molluscs are potentially good indicators of the health of an ecosystem, as many are species-specific predators on a huge variety of marine benthic and sessile invertebrates from almost every taxonomic group. Additionally, they are known to contain bio-compounds of significance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(73 citation statements)
references
References 33 publications
7
60
3
1
Order By: Relevance
“…Specimens were collected in Bunaken National Park (BNP), North Sulawesi, Indonesia during 2015-2016 by scuba diving (Figure 1, Table 1). For details see Eisenbarth et al (2018). One further specimen from Bangka Island, North Sulawesi, Indonesia, collected in 2017, was also included in the analysis, as it looks similar to the new species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimens were collected in Bunaken National Park (BNP), North Sulawesi, Indonesia during 2015-2016 by scuba diving (Figure 1, Table 1). For details see Eisenbarth et al (2018). One further specimen from Bangka Island, North Sulawesi, Indonesia, collected in 2017, was also included in the analysis, as it looks similar to the new species.…”
Section: Methodsmentioning
confidence: 99%
“…A barcoding approach of the Bunaken material from the studies of Eisenbarth et al (2018) and Kaligis et al (2018) revealed that two of the therein mentioned Noumeaella species actually group with the genus Moridilla. This corroborates the difficulty in assigning specimens correctly to the genera mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…Bunaken National Park in North Sulawesi is one location that well surveyed. Four surveys by Eisenbarth et al 2018 documented more than 200 species, which approximate 50% of the specimens have been identified, and the rest still unknown. In this study, a total of 13 specimens were collected and identified based on the morphological characteristics according to identification book "Nudibranch Behavior" (Behrens et al 2005).…”
Section: Identification Of Nudibranchmentioning
confidence: 99%
“…The several specimens belonging to C. lochi were 18-SM-N-3, 18-SM-N-6, 18-SM-N-7, 18-SM-N-10, and 18-SM-S-7. Specimen 18-SM-N-14 is suggested as C. annae because of its blue with darker markings and lack of a mid-dorsal longitudinal line; small black specks within the blue areas (Eisenbarth et al 2018). At this location, three different species of genus Phyllidiopsis were collected and identified as P. pipeki (18-SM-N-2), P. fissurata (18-SM-N-8), and P. krempfi (18-SM-S-11).…”
Section: Identification Of Nudibranchmentioning
confidence: 99%
“…The Indonesian archipelago is a hotspot for biodiversity in the world (Gastropoda et al, 2018). Studies regarding the screening of secondary metabolites-producing bacterial symbionts are important for understanding their biotechnological potential (Radjasa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%